2019
DOI: 10.4314/ahs.v19i1.50
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of propofol and ketofol (Ketamine-Propofol mixture) on emergence agitation in children undergoing tonsillectomy

Abstract: Background The aim of this study was to compare the effect of propofol and ketofol (ketamine-propofol mixture) on EA in children undergoing tonsillectomy. Method In this randomized clinical trial, 87 ASA class I and II patients, aged 3–12 years, who underwent tonsillectomy, were divided into two groups to receive either propofol 100 µg/kg/min (group p, n=44) or ketofol : ketamine 25 µg/kg/min + propofol 75 µg/kg/min (group k, n= 43). Incidence and severity of EA was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The incidence and severity of ED were measured by PAED score. Interestingly, no statistical difference could be found [48].…”
Section: Ketaminementioning
confidence: 82%
“…The incidence and severity of ED were measured by PAED score. Interestingly, no statistical difference could be found [48].…”
Section: Ketaminementioning
confidence: 82%
“…At present, analgesics and sedatives are mainly used for the treatment of restlessness and pain. Some studies [9] show that some analgesics can relieve the pain after operation, but have the risk of bronchospasm, respiratory depression, nausea and vomiting, and prolong the recovery time. Some studies have shown that children depend heavily on their parents [18].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main ways to reduce postoperative restlessness and relieve postoperative pain are drug and psychological intervention. But drug treatment can prolong the recovery time and increase the occurrence of adverse reactions after operation [9]. Li Lei [10] used preoperative games to reduce the incidence of postoperative agitation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands, Jalili et al, who compared the effect of propofol and ketofol on emergence delerium in 87 ASA I and II children aged from 3-12 years and underwent adenotonsillectomy, reported no statistically signi cant difference between the two groups regarding HR in the recovery room at 0, 10, and 20 minutes postoperatively. (19) The smoothness of extubation without coughing, laryngospasm and vomiting on the tube was examined in both groups and it was in favor of ketofol group.…”
Section: Discussionmentioning
confidence: 99%